2015
DOI: 10.1002/we.1826
|View full text |Cite
|
Sign up to set email alerts
|

An economic impact metric for evaluating wave height forecasters for offshore wind maintenance access

Abstract: This paper demonstrates that wave height forecasters chosen on statistical quality metrics result in sub-optimal decision support for offshore wind farm maintenance. Offshore access is constrained by wave height, but the majority of approaches to evaluating the effectiveness of a wave height forecaster utilize overall accuracy or error rates. This paper introduces a new metric more appropriate to the wind industry, which considers the economic impact of an incorrect forecast above or below critical wave height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…For example, [8] presents operational wave height limits for various forms of transportation, including helicopters and sea vessels to improve the ability to schedule maintenance, reducing costs related to vessel dispatch and recall due to unexpected wave patterns. Catterson et al (2016), [9], proposed an economic forecasting metric (EFM) which considers the economic impact of an incorrect forecast above or below critical wave height boundaries. In this study, a methodology is described for formulating criterion where the connection between forecasting error and economic consequences are amplified in terms of opportunity cost.…”
Section: Related Work Of Forecasting Using Data-driven Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, [8] presents operational wave height limits for various forms of transportation, including helicopters and sea vessels to improve the ability to schedule maintenance, reducing costs related to vessel dispatch and recall due to unexpected wave patterns. Catterson et al (2016), [9], proposed an economic forecasting metric (EFM) which considers the economic impact of an incorrect forecast above or below critical wave height boundaries. In this study, a methodology is described for formulating criterion where the connection between forecasting error and economic consequences are amplified in terms of opportunity cost.…”
Section: Related Work Of Forecasting Using Data-driven Methodsmentioning
confidence: 99%
“…Significant economic benefits (of at least £55,350 per annum) resulted from applying RMSE instead of EFM for the 8 hr ahead case study. Taylor and Jeon (2018), [10], extended the work of [9] by incorporating probabilistic forecasting and examined whether a probabilistic approach to decision making is more effective than the deterministic approach used in [9]. They concluded that the wave height forecast by the probabilistic approach is the most accurate and should be included in the decisionmaking process of whether or not to launch service vehicles for offshore turbines.…”
Section: Related Work Of Forecasting Using Data-driven Methodsmentioning
confidence: 99%
“…In this case the forecast representation can be discrete, e.g., probability of having wind speed below 4 m/s during an X hours window. The economic cost for deterministic forecast errors is therefore dependent on whether the forecasts and realizations fall on the same side of the threshold or not which makes forecast evaluation challenging [155] and is a strong argument for taking a probabilistic approach.…”
Section: Maintenance Scheduling Of Wind Power Plantsmentioning
confidence: 99%
“…In practice, this This work is supported by the EPSRC Supergen Wind Hub project ORACLES, EP/L014106/1. 978-1-7281-1450-7/19/$31.00 ©2019 IEEE currently translates as single-valued deterministic forecasts of significant wave height obtained via Numerical Weather Prediction (NWP) models for horizons of over approximately 6 hours [2], [3]. This information is assimilated along with information flows from assets, other important weather variables (lightning risk, visibility, etc), and live point measurements by the marine coordination team who then use this information, the current schedule, and site expertise to execute operation and maintenance each day.…”
Section: Introductionmentioning
confidence: 99%